Influence on Prices, Quality of Service and Distribution on Palm Oil Crude Purchase Decisions at PT Bangun Sempurna Lestari Medan - Rosinta Romauli Situmeang; Eric Halim; Stefanny Stefanny (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to discuss and analyze the Price, Service Quality and Distribution of the Decision to Purchase Crude Palm Oil at PT Bangun Sempurna Lestari Medan. The population and sample in this study were 64 CPO customer participants. The research method uses multiple linear regression analysis techniques. The partial hypothesis calculation results obtained tcount> ttable or 2.806> 2,000 and the significant obtained 0.007 <0.05, means the partial significance of positive and significant prices on CPO purchases at PT Bangun Sempurna Lestari. The calculation result of hypothesis testing partially obtained tcount> ttable or 2.193> 2,000 and the significant obtained was 0.032 <0.05, meaning partial significance. Positive and significant service to CPO purchases at PT Bangun Sempurna Lestari. The partial hypothesis calculation results obtained tcount> ttable or 2.059> 2,000 and the significant obtained 0.044 <0.05, meaning partial. Positive and significant distribution of CPO purchases at PT Bangun Sempurna Lestari. The test results obtained calculated F value (11,240)> F table (2.76) and a significance probability of 0.000 <0.05, the simultaneous significance of Price, Service Quality and Distribution is positive and significant for CPO Purchasing Decisions at PT Bangun Sempurna Lestari.